Bronchopulmonary dysplasia in children: clinical and anamnestic aspects of cytokine gene polymorphisms - S. V. Suprun; N. O. Abdulina; E. N. Suprun; E. B. Nagovitcina; S. V. Pichugina; T. А. Sorvina (Аллергология и Иммунология в Педиатрии)
Introduction. Bronchopulmonary dysplasia (BPD) is a chronic diffuse parenchymal lung disease mainly in premature infants with a wide range of risk factors. In the tissues of the immature lung, inflammatory reactions are triggered with increased production of cytokines, which are controlled by candidate genes and contribute to the formation of BPD. The aim of the study was to study the clinical and anamnestic aspects of polymorphisms of cytokine genes IL-4, IL-6, IL-10, TNFa, regulating inflammation, as a predisposition factor for the development of BPD in children on the example of the Amur region.Material and methods. 80 children were examined, 58 of them with BPD (the main group), 22 without this disease (the comparison group). Clinical and anamnestic data were collected, single nucleotide polymorphisms of IL-4 (C589T), IL-6 (C174G), IL-10 (G1082A, C592A, C819T), TNFa (G308A) genes were determined by Real-time PCR.Results. Indicators of gestational age, body weight, and Apgar scores at the 1st and 5th minutes in children with BPD were lower than in the comparison group. In patients with BPD, 89.66 % of cases revealed the presence of respiratory distress syndrome (RDS) in the neonatal period. When assessing the frequency of occurrence of polymorphic variants of cytokine genes, differences were revealed: in the main group, the GA genotype of the IL-10 gene (G1082A) was determined statistically significantly less frequently than in the comparison group (p < 0.05). Trends were noted in children with BPD with polymorphic variants of the following genes: IL-6 (C174G), IL-10 (G1082A), IL-10 (C819T), TNFa (G308A) — decrease in birth weight; IL-10 (G1082A), IL-10 (C819T) — increase RDS frequencies; IL-4 (C589T), IL-10 (G1082A), IL-10 (C819T), TNFa (G308A) — increased duration of ventilation; IL-6 (C174G), IL-10 (C819T), (C592A) — increased duration of CPAP.Conclusions. In the conducted study, cytokine gene polymorphisms were detected in children with BPD in the region more often IL-4 (C589T) — CC; IL-10 (G1082A) — GG, AA; IL-10 (C592A) — CC and less frequently IL-4 (C589T) — CT; IL- 10 (G1082A) — GA; IL-10 (C592A) — CA. The noted trends in clinical and anamnestic data and information on the carriage of polymorphic variants of cytokine genes in children with BPD make it possible to develop prognostic scenarios for the development of BPD in the neonatal and postnatal periods.